2021
DOI: 10.1016/j.scriptamat.2020.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Imparting high-temperature grain stability to an Al-Mg alloy

Abstract: Al alloys, despite their excellent strength-to-weight ratio, cannot be used at elevated temperatures because of microstructural instability owing to grain growth and precipitate coarsening, thus, leading to a drastic loss in their strength. In this work, we have attempted to address the issue of grain growth by introducing in-situ formed polymer derived ceramics in an Al-Mg alloy. A stable grain structure with minimal loss in hardness when exposed to 450 °C and 550 °C for 1 hour was obtained due to the particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Furthermore, the amplitude of the serrations in the tensile curve of the composite due to the Portevin-Le Chatelier (PLC) effect was reduced. In another study (by the present authors), it was found that this composite also possesses stability in both grain size and strength when exposed to a temperature of 550°C for 1 hr [28].…”
Section: Introductionsupporting
confidence: 55%
“…Furthermore, the amplitude of the serrations in the tensile curve of the composite due to the Portevin-Le Chatelier (PLC) effect was reduced. In another study (by the present authors), it was found that this composite also possesses stability in both grain size and strength when exposed to a temperature of 550°C for 1 hr [28].…”
Section: Introductionsupporting
confidence: 55%
“…However, Griffiths et al noted that coarsening of grain boundary Al 3 Zr particles during an 8 h heat treatment at 400°C or long-term creep tests at 260°C decreased their ability to inhibit sliding of the ∼1 μm grains, leading to decreased tensile and creep strengths [47]. Thermally stable ceramic dispersions are also ideal candidates for restricting grain growth [203]. Although TiN [154,191] and TiB 2 [147] particles restrict grain growth during AM fabrication by Zener pinning, their effectiveness in restricting grain growth in AM alloys at elevated temperatures has not been investigated.
Figure 15. Grain boundary pinning by Al 3 (Sc,Zr) and Mg 2 Si precipitates in LPBF-processed Al–14.1Mg–0.47Si–0.31Sc–0.17Zr.
…”
Section: High-temperature Mechanical Properties and Thermal Stabilitymentioning
confidence: 99%
“…Of these strategies, the latter two appear to be achievable based on existing literature. The presence of precipitates such as Al 3 (Zr,Sc) along grain boundaries has been shown to pin grain boundaries and prevent grain growth in AM high-temperature alloys [70,98,115,116] (Figure 15) and ceramic particles are utilised to the same effect in cast Al alloys [203], although the effect has not been studied in AM CDAs. The pinning effect is also expected to decrease GBS during creep and may also reduce the effective grain boundary diffusion rate.…”
Section: High-temperature Mechanical Properties and Thermal Stabilitymentioning
confidence: 99%
“…After ECAP-BP-RT, according to Equation (9), in an elastic matrix with E(673) ≈ 0.93E(293) [48], the gas pressure inside the crack would reach 1.46 P 0 =362 MPa (3.62 bars) at 400 • C, more than enough to propagate cracks, especially considering their multiplicity and interactions. According to Equation (7), COD max would exceed 1 µm for a crack radius of 75 µm, and 5 µm for a radius of 375 µm. These elastic estimates are in the same order of magnitude as the measured lengths of the Al nano-filaments that bridge the cracks.…”
Section: Thermally Induced Damagementioning
confidence: 99%